Investigation of Visual Stimulus With Various Colors and the Layout for the Oddball Paradigm in Evoked Related Potential-Based Brain–Computer Interface - Guo, Miaoji; Jin, Jing; Jiao, Yong; Wang, Xingyu; Cichockia, Andrzej (Frontiers in Computational Neuroscience, 2019)
Objective: Stimulus visual patterns, such as size, content, color, luminosity, and interval, play key roles for brain–computer interface (BCI) performance. However, the three primary colors to be intercompared as a single variable or factor on the same platform are poorly studied. In this work, we configured the visual stimulus patterns with red, green, and blue and designed a novel layout of the BCI interface to study the waveforms and performance of the evoked related potential (ERP). Approach: Twelve subjects participated in our experiment, which was composed of three different color sub-experiments. Four blocks of the interface were presented along the edge of the screen, and the other four were assembled in the center, to investigate the problem of adjacency distraction. Repeated-measures ANOVA and Bonferroni correction were applied for statistical analysis. Main results: The averaged online accuracy was 98.44% for red paradigm, higher than 92.71% for green paradigm and 93.23% for blue paradigm. Furthermore, significant differences in online accuracy (p<0.05) and information transfer rate (p<0.05) were found between red and green paradigms. Significance: The red stimulus paradigm yielded the best performance. The proposed design of ERP-based BCI was practical and effective for many potential applications.